Provision of e-services in Governmental and Inter-governmental Agencies - Ludmila Tereshchenko (Право. Журнал Высшей школы экономики, 2013)
Tereshchenko Ludmila - Leading research fellow at the Higher School of Economics’ Educational and Research Laboratory for Information Law; Professor of Legal Sciences, Doctor of Law. Address: 20 Myasnitskaya str., Moscow, 101000, Russian Federation. E-mail: tereshchenko@post.ruThis article analyses issues relevant to the provision of governmental services using information and communication technologies at both national and intergovernmental levels. It considers the coordination problems facing state agencies that offer governmental and municipal services, including the need for universal technological solutions and coordination of information systems. This article also examines the experiences of trans-border electronic public service provision across European Union countries and considers solutions to the problem of coordinating public services provision.